Does FTA Import Utilization Enhance Firm Performance? An Assessment of the Philippine Manufacturing Sector - Neil Irwin S. Moreno; Francis Mark A. Quimba; Abigail E. Andrada (Philippine Institute for Development Studies (PIDS), 2023)
This study assessed how utilizing free trade agreements (FTAs) in imports affects the performance of Philippine manufacturing firms. It utilized recent developments in differencesin-differences (DID) estimation with multiple time periods and variation in treatment timing. This DID method was applied to a rich Philippine microdata set that integrates the annual firm surveys/censuses with import transactions data. The empirical analysis reveals that the FTA import utilization effects varied across different groups and periods; some estimates did not even have the expected signs. Overall, productivity gains were limited for importers that started to use FTAs. However, the productivity losses observed from quitting FTA use suggest potential long-run productivity gains obtained by consistent FTA users. The results also confirm the trade-facilitating effects of FTAs, as FTA starters consistently experienced substantial import growth. Meanwhile, quitting use only generated short-term adverse effects on firm imports, implying that some importers might have eventually increased their imports from non-FTA partners. Among others, policymakers must prioritize easing FTA procedures, intensify firm support mechanisms, and improve data access and monitoring. The country's ongoing effort in monitoring import surges could be leveraged to also identify sectors that heavily rely on imported intermediate inputs. This could be crucial in facilitating their participation and upgrading in global value chains.
Keywords: 330; free trade agreements; firm performance; import facilitation; difference-indifferences; doubly robust